An Enhanced Physically Based Scour Model for Considering Jet Air Entrainment. (September 2016) - Duarte, Rafael; Pinheiro, António; Schleiss, Anton J.
Abstract: Based on systematic experiments on the influence of air entrainment on rock block stability in plunge pools impacted by high-velocity jets, this study presents adaptations of a physically based scour model. The modifications regarding jet aeration are implemented in the Comprehensive Scour Model (CSM), allowing it to reproduce the physical-mechanical processes involved in scour formation concerning the three phases; namely, water, rock, and air. The enhanced method considers the reduction of momentum of an aerated jet as well as the decrease of energy dissipation in the jet diffusive shear layer, both resulting from the entrainment of air bubbles. Block ejection from the rock mass depends on a combination of the aerated time-averaged pressure coefficient and the modified maximum dynamic impulsion coefficient, which was found to be a constant value of 0.2 for high-velocity jets in deep pools. The modified model is applied to the case of the observed scour hole at the Kariba Dam, with good agreement.